Influence of Radioiodine Therapy on Urinary Iodine Excretion - Melier, B.; Lauer, I.; Bähre, M.; Richter, E. (Nuklearmedizin - NuclearMedicine, 1998)
Aim: In 214 patients with benign thyroid diseases the time-course of urinary iodine excretion (UIE) was investigated in order to identify changes after radioiodine therapy (RITh). Method: UIE was measured photometrically (cerium-arsenite method) and related to urinary creatinine on the first and last day of the radioiodine test and then three days, seven days, four weeks, and six months after 1311 administration. Results: As compared with the level found immediately before radioiodine therapy, median UIE had almost doubled four weeks after therapy and was still significantly elevated six months after therapy. This increase correlated significantly with the target volume as measured by scintigraphy and sonography. Conclusions: The persistent elevation of UIE for months after RITh is a measure of treatment-induced damage to thyrocytes. Therefore, in view of the unfavourable kinetics of iodine that follow it, RITh should if possible be given via a single-dose regime.
Keywords: Urinary iodine excretion; radioiodine test; radioiodine therapy